Ruxolitinib improves symptoms and quality of life in a patient with systemic mastocytosis. Issue 1 (December 2016) - Yacoub, Abdulraheem; Prochaska, Lindsey
Abstract Background Systemic mastocytosis is a clonal myeloproliferative neoplasm associated with constitutional symptoms from mast cell mediated chemical and cytokine release. According to the literature, Ruxolitinib, a JAK1/JAK2 inhibitor, has been shown to reduce symptoms related to proinflammatory cytokine release in other myeloproliferative neoplasms. Case presentation Here we present a case using Ruxolitinib for disabling constitutional symptoms despite complete bone marrow response in a patient with aggressive systemic mastocytosis. Assessment tools used to monitor symptoms in previously published Ruxolitinib trials were adopted to track symptom improvement and quality of life. Conclusions Ruxolitinib significantly improved symptoms and quality of life in our patient with systemic mastocytosis.